2014
DOI: 10.1242/jeb.093831
|View full text |Cite
|
Sign up to set email alerts
|

Use of the swim bladder and lateral line in near-field sound source localization by fishes

Abstract: We investigated the roles of the swim bladder and the lateral line system in sound localization behavior by the plainfin midshipman fish (Porichthys notatus). Reproductive female midshipman underwent either surgical deflation of the swim bladder or cryoablation of the lateral line and were then tested in a monopolar sound source localization task. Fish with nominally 'deflated' swim bladders performed similar to sham-deflated controls; however, postexperiment evaluation of swim bladder deflation revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
(70 reference statements)
1
37
0
Order By: Relevance
“…pomacentrids (Myrberg and Spires 1980), cods (Sand and Hawkins 1973) and midshipman (Coffin et al 2014)], suggesting species differences in the ability to detect pressure. However, these studies do not rule out the possibility of an unknown conducting pathway between the bladder and the ears (see treatment of pomacentrid sound production below) requiring further work to settle this question.…”
Section: Swimbladder As An Auditory Organmentioning
confidence: 99%
“…pomacentrids (Myrberg and Spires 1980), cods (Sand and Hawkins 1973) and midshipman (Coffin et al 2014)], suggesting species differences in the ability to detect pressure. However, these studies do not rule out the possibility of an unknown conducting pathway between the bladder and the ears (see treatment of pomacentrid sound production below) requiring further work to settle this question.…”
Section: Swimbladder As An Auditory Organmentioning
confidence: 99%
“…However, although the capacity for directional hearing in fish is relatively well described [14], only a handful of experimental studies have tested how it is mediated. These studies have shown that both sound pressure and particle motion can play very different, and independent roles in the oriented movement of fish seeking a sound source (positive phonotaxis) [59]. In contrast, although sound induced repulsion (negative phonotaxis) has also been described in a few species of fish, the sensory cues responsible for these responses have not yet been explicitly described so are unknown [1014].…”
Section: Introductionmentioning
confidence: 99%
“…Propagation of reef sounds is likely to vary considerably based on source amplitude and spectral characteristics, bathymetry, bottom type, sea state, temperature, and salinity (Rogers and Cox, 1988). While some recent investigations of fish orientation behavior have directly measured particle motion in the lab (e.g., Zeddies et al, 2012;Coffin et al, 2014), until recently there have been no direct field measurements of coral reef acoustic particle motion. Such field measurements of both particle motion and sound pressure at a range of distances from a reef are required to assess the distances over which reef sound might act as a relevant cue for settlement-stage larval fishes and invertebrates.…”
Section: The Propagation Of Reef Soundscapesmentioning
confidence: 99%